Fiber Optic Sensor for Simultaneous Measurement of pH and Dissolved Oxygen - Deepa, N.; Ganesh, A. Balaji (Applied Mechanics and Materials, 2014)
The work describes the constructions of optical fiber based minimal invasive sensing system to measure pH and dissolved oxygen using sol-gel membranes which are attached internally in any transparent container. The disposable sensing membranes are very thin size and prepared as fluorescent dye doped in silica film using simple procedures. The sensor characteristics such as response time, linearity, repeatability and reversibility are evaluated and the performance of the sensor also compared with commercial meters. The experiments such as, chemical stability and photo stability are also carried out. The detection limit of pH sensor is found between 3 pH and 10 pH, however good sensitivity is obtained for the ranges from 4 pH and 9 pH with the response time of 7 seconds. Non-linear response is obtained for dissolved oxygen sensor and it is made linear by applying Stern-Volmer equation. The oxygen sensor shows good sensitivity in the ranges from 2 mg/L to 8 mg/L.